Angiogenesis, thrombospondin, and ductal carcinoma in situ of the breast. Issue 8 (1st August 2002) - Rice, A; Quinn, C M
Abstract : Angiogenesis, the growth of new vessels from existing vasculature, plays an essential role in tumour development. The process involves interaction between a variety of cells, growth factors, and components of the extracellular matrix, regulated by pro-angiogenic and anti-angiogenic factors. This review profiles these factors, outlines the available methods for measuring new vessel formation, and discusses the importance of angiogenesis in breast cancer, with emphasis on ductal carcinoma in situ.